2000
DOI: 10.1001/archpedi.154.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risks for Cervical Human Papillomavirus Infection and Squamous Intraepithelial Lesions in Adolescent Girls

Abstract: High prevalence of HPV infection in both groups underscores the risky sexual behavior in this adolescent cohort. Rates of HPV infection and SILs were higher among HIV-infected girls, despite similar sexual risk behaviors and the relatively healthy state of our HIV-infected group. Infection with HIV may enhance HPV proliferation through mechanisms other than CD4 immunosuppression, particularly early in the course of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
1
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 32 publications
4
58
1
9
Order By: Relevance
“…Moscicki et al found prevalence rates of 54.5% for all genital HPV types and 29.1% for HR HPV types in a cross-sectional study of adolescent females [10]. The youngest women in a longitudinal study of college-aged women by Ho et al had the highest prevalence of HPV infection.…”
Section: Discussionmentioning
confidence: 96%
“…Moscicki et al found prevalence rates of 54.5% for all genital HPV types and 29.1% for HR HPV types in a cross-sectional study of adolescent females [10]. The youngest women in a longitudinal study of college-aged women by Ho et al had the highest prevalence of HPV infection.…”
Section: Discussionmentioning
confidence: 96%
“…Evidences showed that, immunosuppression and low CD4 counts caused by HIV infection predisposes women living with HIV infection at an increased risk for cervical cancer and the development of squamous intraepithelial lesions [5][6][7][8][9]. Cervical cancer is about 8 times more common in HIV infected women than none infected ones [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer usually affects women of middle or older age, but it may be diagnosed in any reproductive-aged women especially those infected with HIV/AIDS which enhances HPV proliferation (Moscicki et al, 2000;Strickler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%